Pastoral pada Lansia Berbasis Homecare dan Metode Active Listening: Bentuk Pelayanan Gereja di Paroki Maria Ratu Damai Purworejo Donomulyo - Getrudis Seuk; Paskalis Edwin I Nyoman Paska; Laurensius Laka (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
Pastoral care provided by the parish to the elderly is one form of the Church's concern for its people who have entered old age. Pastoral care is carried out with a homecare approach and active listening methods, as a means to support their physical, mental, and spiritual well-being.However, what the parish has done has not been maximized and effective because it does not yet have competent personnel in the field of homecare. The purpose of this study is toTo find out to what extent the parish implements homecare-based elderly pastoral care and active listening methods, both in terms of supporting factors and inhibiting factors as a form of Church service at the Maria Ratu Damai Parish, Donomulyo.The methodology used in this study is qualitative research with a phenomenological approach. Data collection techniques through interviews, observations and documentation. The analysis of data collection used in this study is data processing developed by Colaizzi and Carpenter with the NVIVO software application. The results of the study identified homecare-based elderly pastoral and active listening methods that help pastoral officers to perform optimally and effectively. The supporting factor is the commitment of pastoral officers and medical personnel in implementing homecare with full responsibility. In addition to the factorssupporting factors, there are also inhibiting factors such as limited resources, both manpower and funds. This study shows that the homecare-based pastoral approach and the active listening method are modelsan effective service model that pays attention to the holistic aspects of elderly welfare, involving social, emotional and spiritual aspects in church services in the Parish. Key: Homecare and Active Listening